2010
DOI: 10.1016/j.neuron.2010.07.020
|View full text |Cite
|
Sign up to set email alerts
|

Moral Judgments Recruit Domain-General Valuation Mechanisms to Integrate Representations of Probability and Magnitude

Abstract: Many important moral decisions, particularly at the policy level, require the evaluation of choices involving outcomes of variable magnitude and probability. Many economic decisions involve the same problem. It is not known whether and to what extent these structurally isomorphic decisions rely on common neural mechanisms. Subjects undergoing fMRI evaluated the moral acceptability of sacrificing a single life to save a larger group of variable size and probability of dying without action. Paralleling research … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

22
201
2
4

Year Published

2012
2012
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 226 publications
(229 citation statements)
references
References 69 publications
22
201
2
4
Order By: Relevance
“…According to such theories, moral choices are primarily seen as products of specific morally motivated intuitive and rule-governed processes. Our findings instead support alternative views that stress the continuities between the moral and other choice domains (7,8,39,40). If moral decisions are sensitive to sensorimotor interactions and the complex timing of these, then moral cognition might turn out to have more in common with how motor plans are dynamically updated, compared with following a rule, than previously hypothesized.…”
Section: Discussioncontrasting
confidence: 58%
“…According to such theories, moral choices are primarily seen as products of specific morally motivated intuitive and rule-governed processes. Our findings instead support alternative views that stress the continuities between the moral and other choice domains (7,8,39,40). If moral decisions are sensitive to sensorimotor interactions and the complex timing of these, then moral cognition might turn out to have more in common with how motor plans are dynamically updated, compared with following a rule, than previously hypothesized.…”
Section: Discussioncontrasting
confidence: 58%
“…The specific role of the bilateral PCC is not clear, but neuroimaging studies on creative thinking have shown that the right PCC is activated in novices operating a digit count task [37]. Neuroimaging studies on the neural correlates of economic and moral decision-making demonstrate that the bilateral PCC (especially the right PCC) is associated with the expected reward probability of expected economic utility [38], expected moral utility, practical moral utility, and event probabilities (primarily right PCC) [39]. The PCC may assist some motor areas in conflict resolution after the prefrontal cortex has monitored the response conflict [40,41].…”
Section: Cingulate Cortexmentioning
confidence: 99%
“…More importantly, we hypothesized that the degree of spatial segregation would provide a neural index of the individual propensity to help others. Given that positive subjective valuation of others' welfare can lead to prosocial decisions (17,(26)(27)(28)(29), we expected to find that decreased segregation would be associated with greater prosociality. In addition, we examined whether and how corticostriatal communications contribute to individual differences in representing and updating self-and other-regarding values.…”
mentioning
confidence: 99%